The Students Perception on The Teaching Learning Writing Activities Using EDMONDO Application - Budiana, Haris (Papanda Publisher, 2024)
Article History: Received yyyy-mm-dd Accepted yyyy-mm-dd Edmodo application is believed to be able to assist teacher in teaching writing to students since it has adequate features to support learning writing activities. The focus of this research is to find out the students’ perception about Edmodo application as a media in learning writing. The writer use qualitative as the research method. The participants are ten grade majoring in Software Enginering of Vocational high school consisting of 34 students by random sampling. To collect the data the writer obtain them by using observation, questionnaire, and interview. The result of the study showed that most of the students enjoy learning English using Edmodo Application. However, there is a technical problem dealing with internet connection, storage and incompatible device. Keywords: Edmondo application, writing, perception